Oriental, Black, and White The Formation of Racial Habits in American Theater - Lee, Josephine (University of North Carolina Press, 2022)
In this book, Josephine Lee looks at the intertwined racial representations of nineteenth- and early twentieth-century American theater. In minstrelsy, melodrama, vaudeville, and musicals, both white and African American performers enacted blackface characterizations alongside oriental stereotypes of opulence and deception, comic servitude, and exotic sexuality. Lee shows how blackface types were often associated with working-class masculinity and the development of a nativist white racial identity for European immigrants, while the oriental marked what was culturally coded as foreign, feminized, and ornamental. These conflicting racial connotations were often intermingled in actual stage performance, as stage productions contrasted nostalgic characterizations of plantation slavery with the figures of the despotic sultan, the seductive dancing girl, and the comic Chinese laundryman. African American performers also performed common oriental themes and characterizations, repurposing them for their own commentary on Black racial progress and aspiration. The juxtaposition of orientalism and black figuration became standard fare for American theatergoers at a historical moment in which the color line was rigidly policed. These interlocking cross-racial impersonations offer fascinating insights into habits of racial representation both inside and outside the theater.